Effects of different fertilization levels on the concentration of high molecular weight glutenin subunits of two spring, hard red bread wheat cultivars. Issue 6 (3rd September 2019) - Tóth, Brigitta; van Biljon, Angeline; Moloi, Makoena Joyce; Labuschagne, Maryke
Abstract: Backgrounds and objectives: High molecular weight gluten subunits (HMW‐GS) are generally considered to play a key role in gluten formation and structure and are closely related to wheat quality. In this study, two spring wheat cultivars (PAN3497 and SST806) with the same HMW‐GS composition (1Ax1, 1Bx7, 1By8, 1Dx2, and 1Dy12) were tested in the greenhouse, over 2 years, in order to determine how different genetic backgrounds, and low‐nitrogen and low‐phosphorus treatments, influenced the expression and quantity of the HMW‐GS, as measured by reverse‐phase high‐performance liquid chromatography (RP‐HPLC). Findings: Cultivar effect was highly significant for all HMW‐GS, except for 1By8. A large treatment effect was found on subunits 1Ax1, 1Dy12, and 1By8. Cultivar‐by‐treatment interaction was highly significant and contributed to variation of subunit 1Dx2. Subunits 1Dy12 and 1By8 were highly influenced by low‐N conditions. Ratio of HMW‐GS x type/y type was higher for PAN3497 than for SST806. Furthermore, a strong treatment effect was observed for the ratio of x type/y type, which was 45% higher in PAN3497 under optimal and low‐N conditions, compared to SST806. Conclusions: This study showed that fertilization level had a considerable effect on HMW‐GS composition and on FPC, with low‐N conditions having the largest influence, followed by a combination of low N and low P. Significance and novelty: The results highlighted the importance of the y‐type subunits in the bread wheat quality breeding programs, especially under low‐N and low‐P growing conditions.